L’égalité professionnelle, un espace relationnel en quête de sens - Christine Gautier Chovelon (Éducation et Socialisation)
This article highlights the conceptual and pedagogical tools to explore what real professional equality could be, facilitating openness and decompartmentalization in the male-female relationship. The elaboration of such a space would be based on the necessary emancipatory awareness of men and women's a priori, their conditioning and their practical habits. The link between equality and gender diversity is the support. To this end, a self-training process has been experimented with the support of the coat of arms workshop to promote the quest for meaning. A work of awareness of our perceptions and our symbolic resonances has been put in place an emotional dynamic has emerged around a set of images. The results of this experimentation will be presented showing ways of realization around an ethical requirement and a formative reciprocity.